Curriculum Change in English Language Education in the State of Rajasthan The Dilemmas and Paradoxes - Meganathan, Ramanujam (JOURNAL OF INDIAN EDUCATION, 2013)
This paper presents experiences from the ongoing curricular revision in English Language Education in the Indian State of Rajasthan. While attempting to provide an insider perspective of the understanding of curriculum change and innovation by various stake holders of education, it seeks to answer some questions from the point of view of a curriculum and materials developer. The questions are: (i) How is the idea of syllabus as an operational construct perceived and understood by the syllabus designers and material developers?; (ii) How do the curriculum and syllabus developers and materials designers perceive what should be the methods of teaching-learning of English language?; (iii) How is the process of curriculum change bridge the knowledge gap between and among the various participants of curriculum change? The paper consists of five sections. In the first section the context and backdrop of the initiative of curriculum change is described bringing in the need and intensions of curriculum change. The second section raises the issue of ‘what’ and ‘how’ of syllabus design and the way people involved in curriculum and syllabus development perceived and responded to the change and how the post method condition (whether it exists or not) in the present context of English language education in India impacts the development of materials. The third section raises some questions about materials development for English language education. The fourth section presents the innovations attempted in the curriculum revision exercise. In the last section the paper discusses the lessons learnt from the processes of curriculum revision and materials development.